2024
DOI: 10.1039/d3nh00364g
|View full text |Cite
|
Sign up to set email alerts
|

Enriching 2D transition metal borides via MB XMenes (M = Fe, Co, Ir): Strong correlation and magnetism

Jiawei Tang,
Shaohan Li,
Duo Wang
et al.

Abstract: Recently, two-dimensional (2D) FeSe-like anti-MXenes (or XMenes), composed of late d-block transition metal M and p-block nonmetal X elements, have been both experimentally and theoretically investigated. Here, we select three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Recent studies, such as those by Jinxing et al , 39 have demonstrated the promising potential of anti-MXenes in catalytic applications. Additionally, Jiawei et al 40 have investigated three anti-MXene borides (FeB, CoB, and IrB) and highlighted their strong correlation effects and magnetic properties, further underscoring their relevance and importance in the field of materials science. In this investigation, we methodically explore the NRR catalysis capabilities of anti-MXene borides (TMBs), postulating that the encapsulation of transition metals by boron layers substantially contributes to the activation process in the NRR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, such as those by Jinxing et al , 39 have demonstrated the promising potential of anti-MXenes in catalytic applications. Additionally, Jiawei et al 40 have investigated three anti-MXene borides (FeB, CoB, and IrB) and highlighted their strong correlation effects and magnetic properties, further underscoring their relevance and importance in the field of materials science. In this investigation, we methodically explore the NRR catalysis capabilities of anti-MXene borides (TMBs), postulating that the encapsulation of transition metals by boron layers substantially contributes to the activation process in the NRR.…”
Section: Introductionmentioning
confidence: 99%